Inspirations of Cobalt Oxide Nanoparticle Based Anticancer Therapeutics - Huanshao Huang; Jiajun Wang; Junai Zhang; Jiye Cai; Jiang Pi; Jun-Fa Xu (MDPI AG, 2021)
Cobalt is essential to the metabolism of all animals due to its key role in cobalamin, also known as vitamin B12, the primary biological reservoir of cobalt as an ultra-trace element. Current cancer treatment strategies, including chemotherapy and radiotherapy, have been seriously restricted by their side effects and low efficiency for a long time, which urges us to develop new technologies for more effective and much safer anticancer therapies. Novel nanotechnologies, based on different kinds of functional nanomaterials, have been proved to act as effective and promising strategies for anticancer treatment. Based on the important biological roles of cobalt, cobalt oxide nanoparticles (NPs) have been widely developed for their attractive biomedical applications, especially their potential for anticancer treatments due to their selective inhibition of cancer cells. Thus, more and more attention has been attracted to the preparation, characterization and anticancer investigation of cobalt oxide nanoparticles in recent years, which is expected to introduce novel anticancer treatment strategies. In this review, we summarize the synthesis methods of cobalt oxide nanoparticles to discuss the advantages and restrictions for their preparation. Moreover, we emphatically discuss the anticancer functions of cobalt oxide nanoparticles as well as their underlying mechanisms to promote the development of cobalt oxide nanoparticles for anticancer treatments, which might finally benefit the current anticancer therapeutics based on functional cobalt oxide nanoparticles.